2013
DOI: 10.1186/1749-8546-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence for the hepatoprotective activities of the medicinal mushroom Antrodia cinnamomea

Abstract: Antrodia cinnamomea (AC) is an endemic mushroom species of Taiwan, and has been demonstrated to possess diverse biological and pharmacological activities, such as anti-hypertension, anti-hyperlipidemia, anti-inflammation, anti-oxidation, anti-tumor, and immunomodulation. This review focuses on the inhibitory effects of AC on hepatitis, hepatocarcinoma, and alcohol-induced liver diseases (e.g., fatty liver, fibrosis). The relevant biochemical and molecular mechanisms are addressed. Overall, this review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…It grows naturally in the hollow trunk of the old Cinnamomum kanehirai tree or through artificial culture on host wood sections. Due to its versatile biomedical activities, AC is highly valued (12)(13)(14)(15)(16) and Taiwanese forests are threatened with the illegal logging of Cinnamomum kanehirai trees. This study developed a solid-state culture method for AC product to combat this serious illegal logging problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It grows naturally in the hollow trunk of the old Cinnamomum kanehirai tree or through artificial culture on host wood sections. Due to its versatile biomedical activities, AC is highly valued (12)(13)(14)(15)(16) and Taiwanese forests are threatened with the illegal logging of Cinnamomum kanehirai trees. This study developed a solid-state culture method for AC product to combat this serious illegal logging problem.…”
Section: Discussionmentioning
confidence: 99%
“…Antrodia cinnamomea (AC) is a Taiwanese fungus species that grows in the hollow trunk of the Cinnamomum kanehirai tree. Previous investigations have indicated that AC may suppress tumor formation (12), enhance the immune system (13), inhibit viral activity and protect the liver (14). It is often used in Taiwanese folk medicine.…”
Section: Improving Insulin Resistance With Antrodia Cinnamomea Mycelimentioning
confidence: 99%
“…Because of the difficulty in producing A. cinnamomea, as well as its high market price, A. salmonea is often used as a substitute for A. cinnamomea in the marketplace. So far, more than 250 scientific papers have been published on A. cinnamomea [1,[5][6][7], but literature on A. salmonea is rare. To our knowledge, around ten research articles have been published on A. salmonea to date.…”
Section: Fruiting Bodiesmentioning
confidence: 99%
“…The mushroom Antrodia camphorate has anti-hepatic fibrosis activities in vitro [93]. Hepatoprotective activities, including anti-hepatitis, anti-hepatocarcinoma and anti-alcoholism, of mushroom Antrodia cinnamomea have been demonstrated both in vitro and in vivo [94]. In addition, consumption of mushroom Phellinus linteus could prevent tacrine-induced hepatotoxicity [95].…”
Section: Other Bioactivities Of Mushroomsmentioning
confidence: 99%